Deep Eutectic Solvents: A Review of Fundamentals and Applications - Hansen, Benworth B; Spittle, Stephanie; Chen, Brian; Poe, Derrick; Zhang, Yong; Klein, Jeffrey M; Horton, Alexandre; Adhikari, Laxmi; Zelovich, Tamar; Doherty, Brian W; Gurkan, Burcu; Maginn, Edward J; et al. (Chemical reviews, 2021)
Deep eutectic solvents (DESs) are an emerging class of mixtures characterized by significant depressions in melting points compared to those of the neat constituent components. These materials are promising for applications as inexpensive "designer" solvents exhibiting a host of tunable physicochemical properties. A detailed review of the current literature reveals the lack of predictive understanding of the microscopic mechanisms that govern the structure-property relationships in this class of solvents. Complex hydrogen bonding is postulated as the root cause of their melting point depressions and physicochemical properties; to understand these hydrogen bonded networks, it is imperative to study these systems as dynamic entities using both simulations and experiments. This review emphasizes recent research efforts in order to elucidate the next steps needed to develop a fundamental framework needed for a deeper understanding of DESs. It covers recent developments in DES research, frames outstanding scientific questions, and identifies promising research thrusts aligned with the advancement of the field toward predictive models and fundamental understanding of these solvents.